Internet connectivity disruption in Benin (Benin) - Voidly (2026)
CRITICAL severity disruption detected in Benin. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: BJ-2026-0008
Keywords: internet disruption; BJ; disruption; critical